Author program of the course "Knowledge in action» - Yazykova A. V. (Science and education: future development, 2018)
Involving pupils in the teaching and research activities is one of the main directions of the modern educational system which help teachers makе pupils initiative and active. The purpose of the course is the organization conditions which will allow pupils to learn a skill of research and develop research type of thinking.
Keywords: универсальные учебные действия; исследование; проект; научно-исследовательская деятельность; коммуникативная компетентность; Universal educational actions; research; activities; Communicative Competence; отличия; исследовательский тип мышления; сходства; исследовательский инстинкт; шаги исследователя; research project; differences; research type of thinking; similarities; research instinct; the steps of the research